Framing effects in an employee savings scheme: A non-parametric analysis - Peter Kooreman; Bertrand Melenberg; Henriëtte Maria Prast; Nathanaël Vellekoop (Institute for the Study of Labor (IZA), 2013)
Studies have found evidence that seemingly irrelevant details of an income component such as its label have an effect on how it is used. Using a data set with more than one million employee-month observations, we investigate the role of functional form assumptions and time aggregation in the analysis of these effects. In most cases we find evidence that marginal propensities to save differ across income components. Our analysis reveals a large degree of heterogeneity in savings behavior within the year.
Keywords: D13; D91; G23; 330; framing effects; labeling effects; employee savings; nonparametric methods; behavioral economics